Development of measures for position improvement of the specialty “Management of Innovative Activity” SSU on the market of educational services in Ukraine - V.V. Bozhkova; Ya.O. Tymokhina (Marketing i Menedžment Innovacij, 2012)
In this article it is analyzed competitors, demographic and Internet environment of the specialty Management of innovation activity SSU and proposed recommendations to upgrade its position on the Ukraines educational services market.